Small Ball Game Learning Model Through the Application of Simple Tools for Elementary School Students - Muhammad Fadli; M. Imran Hasanuddin; Andi Muhammad Rizky Al Mufarid (Program Pascasarjana Universitas Negeri Jakarta, 2025)
This study aims to develop a small-ball game learning model through the use of simple equipment for elementary school students. The common problems encountered in teaching small-ball games include limited facilities and infrastructure, as well as the lack of learning modifications suited to the characteristics of elementary school students. The research method used is a development study with a Research and Development (R&D) approach. The subjects of the study were 60 fourth- and fifth-grade elementary school students. The learning model was developed by modifying game equipment using simple, easily obtainable materials adjusted to students’ motor abilities. The results show that the small-ball game learning model using simple equipment is effective in improving basic motor skills, learning motivation, and students’ active participation in physical education learning. Expert validation indicates that the model is feasible to implement, with a feasibility rate of 87.5%, and the effectiveness of learning increased by 78.3%. This learning model can serve as an alternative solution for schools with limited facilities to optimize small-ball game learning in elementary schools.